Kānpatirup ratthathammanūn læ prachāthipatai khō̜ng Prathēt Thai : kānsamrūat khwāmkhithen Mư̄ang Thai radap prathēt Phō̜. Sō̜. 2552 (Mūnnithi ʻĒchīa, 2009)
Constitutional reform and democracy in Thailand.